2015
DOI: 10.1111/jbi.12503
|View full text |Cite
|
Sign up to set email alerts
|

Climatic drivers of trait assembly in woody plants in Japan

Abstract: Aim A trait‐based biogeographical approach can be used to shed light on species‐sorting mechanisms that are driven by the interactions between species traits and abiotic conditions along large‐scale gradients. We tested the hypothesis that geographical patterns of woody plant assemblages are driven largely by environmental filtering, in relation to climate harshness and seasonality, acting on key functional traits. Location Japanese archipelago. Methods Using a large‐scale grid‐based dataset of 773 woody speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(74 citation statements)
references
References 56 publications
14
60
0
Order By: Relevance
“…Climate was shown to exert the greatest independent effect on SLA, H and SM. This result is in line with several studies conducted in forest ecosystems (Shiono et al., ; Swenson & Weiser, ; Vanneste et al., ) and confirms the role of climate as a primary macro filter shaping the community mean plant traits. Local environmental factors alone (namely, soil, land use and forest structure) showed a minor role in influencing understorey traits.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Climate was shown to exert the greatest independent effect on SLA, H and SM. This result is in line with several studies conducted in forest ecosystems (Shiono et al., ; Swenson & Weiser, ; Vanneste et al., ) and confirms the role of climate as a primary macro filter shaping the community mean plant traits. Local environmental factors alone (namely, soil, land use and forest structure) showed a minor role in influencing understorey traits.…”
Section: Discussionsupporting
confidence: 92%
“…These studies found climate to be the primary macro filter acting on the functional structure of tree communities (Shiono et al., ; Swenson & Weiser, ). In detail, variables related to climate harshness (minimum/maximum temperature and precipitation) and seasonality (temperature and precipitation seasonality) showed a pervasive effect on key functional traits related to fundamental plant strategies (i.e., specific leaf area, seed mass, plant height; Swenson & Weiser, ; Shiono et al., ). However, local soil properties play a significant role in determining community traits at large scales, both alone and in interaction with climate (Ordonez et al., ; Simpson, Richardson, & Laughlin, ).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, protected areas are relatively scarce in areas of moderate and low elevation (except for coastal areas) and, consequently, not representative of the broader geographical pattern of vascular plant biodiversity. These results indicate that Japan's existing protected areas neither efficiently nor effectively conserve plant diversity associated with a variety of different habitat conditions or functional niches Shiono et al 2015). Although criticizing the current design of Japan's protected areas network may not be helpful, it is important to propose a conservation scheme based on Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Macroecological analyses often describe large scale patterns of species richness (Hawkins et al, ; Jablonski, Huang, Roy, & Valentine, ; Kinlock et al, ), range size (Orme et al, ), and more recently patterns of species traits such a s body size and diet (Gainsbury, Meiri, & Lenoir, ; Olson et al, ; Rodrigues, Olalla‐Tárraga, Iverson, & Diniz‐Filho, ) and community assembly rules, like competition and environmental filtering (Karadimou, Tsiripidis, Kallimanis, Raus, & Dimopoulos, ; Ramm et al, ; Shiono et al, ). Multiple underlying mechanisms have been proposed to explain all these patterns highlighting the roles of climate and energy availability (Evans, Warren, & Gaston, ), landscape heterogeneity (Davies et al, ; Kerr, Southwood, & Cihlar, ; Yoshioka, Fukasawa, Mishima, Sasaki, & Kadoya, ), environmental stability or climate seasonality (Carrara & Vázquez, ) and human pressures (Davies et al, ).…”
Section: Introductionmentioning
confidence: 99%